2020
DOI: 10.1073/pnas.1918759117
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of polythioamide antibiotic backbone formation reveals unusual thiotemplated assembly strategy

Abstract: Closthioamide (CTA) is a rare example of a thioamide-containing nonribosomal peptide and is one of only a handful of secondary metabolites described from obligately anaerobic bacteria. Although the biosynthetic gene cluster responsible for CTA production and the thioamide synthetase that catalyzes sulfur incorporation were recently discovered, the logic for peptide backbone assembly has remained a mystery. Here, through the use of in vitro biochemical assays, we demonstrate that the amide backbone of CTA is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Although the presence of CtaB and a PLP‐dependent decarboxylase (CtaF) in the genetic locus is consistent with such a pathway, we recently demonstrated that CtaF is involved in the assembly of the poly‐βAla backbone of CTA (Figure 1 C). [8a] Thus, we predicted that the diamine core of CTA would originate from a novel pathway involving CtaB and the AKR CtaK.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the presence of CtaB and a PLP‐dependent decarboxylase (CtaF) in the genetic locus is consistent with such a pathway, we recently demonstrated that CtaF is involved in the assembly of the poly‐βAla backbone of CTA (Figure 1 C). [8a] Thus, we predicted that the diamine core of CTA would originate from a novel pathway involving CtaB and the AKR CtaK.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results described herein, we propose a model for the complete biosynthetic pathway to CTA (Scheme 1). The biosynthesis begins with the conversion of chorismate to PHBA by CtaA and the assembly of the amide backbone on CtaE (CtaE‐amido‐ 1 ) by CtaD and CtaF–G [3a, 8a] . Next, CtaE‐amido‐ 1 , is iteratively thioamidated by CtaC to afford CtaE‐ 1 [8b] .…”
Section: Resultsmentioning
confidence: 99%
“…Its biosynthesis, however, has remained enigmatic until recently. Now it was demonstrated that CTA is biosynthesized via a novel thiotemplated peptide assembly line that differs from canonical NRPSs and therefore escaped previous genomic analyses with automated software tools 100,101 . This example showcases the limitations of automated genome mining efforts relying on characterized biosynthetic mechanisms.…”
Section: Genome-guided Discovery Of Natural Products From Unconventional Sourcesmentioning
confidence: 99%
“…In many biosynthetic pathways, however, only a portion of the biosynthetic enzymes are encoded as standalone proteins. Although a pure type II NRPS would require that all biosynthetic enzymes were standalone proteins, such examples are exceedingly rare, 20,21 and type II systems predominantly occur as hybrids with type I NRPS or PKS assembly lines. The standalone portion of the biosynthetic enzymes are most commonly A domains, CPs or A-CP didomains.…”
Section: A Possible Binning System For Ribosome-independent Peptide Assembly Systemsmentioning
confidence: 99%